Contribution of visual thinking on linear development of preschool children group in visual arts education lessons - (:unkn) unknown (Sakarya University, 2016)
This research is prepared in order to uncover imagination and creativity of 5 years old children's art education, by creating their own thoughts through visual symbols. Describing the subject, children's visual, sensory, tactile sensations have been addressed and their identification with the issue has been provided by paying attention to children's intelligence types. By the methods used in the end, each child will be formed in the minds of different visual ideas from each other, it is provided for transferring the material to create their own icons. This study was conducted with 15 randomly selected children who attend kindergarten from age 5 in the Münevver Şefik Fergar Primary School which located in Kadıköy district of Istanbul in the academic year 2014-2015. In the study; case study method of qualitative research methods and participating observation technique was applied. The study documented with photographs, notes were taken by making observations. © The Turkish Online Journal of Educational Technology.